2022
DOI: 10.1093/crocol/otac015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cannabis Use on Inpatient Inflammatory Bowel Disease Outcomes in 2 States Legalizing Recreational Cannabis

Abstract: Background We evaluated the impact of recreational cannabis legalization on use and inpatient outcomes of patients with inflammatory bowel disease (IBD). Methods Hospitalized adult patients in Colorado and Washington before (2011) and after (2015) recreational cannabis legalization were compared by chi-square tests for categorical variables and t-tests for continuous variables. Multivariable regression models adjusting for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…57 The final study examining inflammatory bowel disease (IBD) outcomes in the U.S. found more cannabis users on total parenteral nutrition post-RCL (95% CI: 0.02, 0.89) and lower total hospital costs in users post-RCL (95% CI: −15 717, −1119). 58 No other IBD outcomes differed pre- to post-RCL (eg, mortality, length of stay, need for surgery, abscess incision and drainage).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…57 The final study examining inflammatory bowel disease (IBD) outcomes in the U.S. found more cannabis users on total parenteral nutrition post-RCL (95% CI: 0.02, 0.89) and lower total hospital costs in users post-RCL (95% CI: −15 717, −1119). 58 No other IBD outcomes differed pre- to post-RCL (eg, mortality, length of stay, need for surgery, abscess incision and drainage).…”
Section: Resultsmentioning
confidence: 96%
“…A study based in Colorado and Washington, found that cannabis use rates in inflammatory bowel disease patients significantly increased from 107 users to 413 ( P ⩽ .001) pre to post-RCL. 58 A Canada-based study of women with moderate-to-severe pelvic pain found an increase in the prevalence of current cannabis use following RCL (13.3% to 21.5%; P ⩽ .001). 59 Another Canadian study showed an increase in the prevalence of current cannabis use after RCL among cancer patients (23.1% to 29.1%; P ⩽ .01).…”
Section: Resultsmentioning
confidence: 99%